2013
DOI: 10.3109/1354750x.2013.840801
|View full text |Cite
|
Sign up to set email alerts
|

The association between galectin-3 and occurrence of reinfarction early after first myocardial infarction treated invasively

Abstract: Galectin-3 might be an additional useful biomarker in prediction for reinfarction early after first MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
13
2
Order By: Relevance
“…Hence, with the strength of a prospective cohort study design and of a large cohort of consecutively enrolled patients, our data demonstrate that Gal-3 predicts cardiovascular mortality in patients with CAD regardless of the presence or absence of left ventricular systolic dysfunction. This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events.…”
Section: Subgroup Analysescontrasting
confidence: 56%
See 2 more Smart Citations
“…Hence, with the strength of a prospective cohort study design and of a large cohort of consecutively enrolled patients, our data demonstrate that Gal-3 predicts cardiovascular mortality in patients with CAD regardless of the presence or absence of left ventricular systolic dysfunction. This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events.…”
Section: Subgroup Analysescontrasting
confidence: 56%
“…This finding is at variance with previous reports in the general population, 24 in smaller CAD cohorts, [13][14][15][16] and in a large cohort of patients with angiographically demonstrated CAD. 32 A prognostic role of Gal-3 on nonfatal cardiovascular events could not, however, be confirmed at variance with previous studies, [13][14][15][16] possibly because in those cohorts most of the effect on cumulative end points was driven by heart failure-related events. Another possibility is that adjustment for the Duke CAD Index Score, one of the strongest predictors of cardiovascular events and death in patients with CAD, might have concealed an effect of Gal-3 on these end points in the our study.…”
Section: Subgroup Analysescontrasting
confidence: 56%
See 1 more Smart Citation
“…In the same cohort, the Authors reported Gal-3 might be an independent predictor of re-infarction early after first MI [52].…”
Section: Gal-3 and Prognosismentioning
confidence: 87%
“…Some Authors evaluated the potential role of Gal-3 as a predictive marker of mortality, HF, atrial fibrillation (AF) and re-infarction in ACS patients [8,33,38,[50][51][52].…”
Section: Gal-3 and Prognosismentioning
confidence: 99%